DEVELOPMENT OF AN AUTONOMOUS ROBOTIC HAND WITH HUMAN INTERACTION CAPABILITIES - KELLY, KEVIN (My University, 2012)
A multiple degree-of-freedom hand has been developed which can interact with a human on a fundamental level. Th e robotic hand is closely modelled on a human hand, consisting of four fingers a nd a thumb. The digits are actuated using five servo motors to provide independen t motion and control. The robotic hand uses a webcam and artificial intelligence to detect and process a user’s hand position. This human interaction capab ility has allowed the robotic hand to perform simple operations such as playin g a human in a game of rock paper scissors. The latter has been showcased at a number of events to promote engineering as a career choice. Basic artificial intelligence has been inte grated into the system to allow the robotic hand to process and react to a video input stream. This has been used to allow the hand to make a more inform ed choice based on the current scenario. Potential future applications of the r obotic hand in manufacturing are explored. KEYWORDS:
29th International Manufacturing Conference
PUBLISHED
Belfast, Ireland
Keywords: Student Recruitment; Robotics